Genomic and phylogenomic exploration of Vibrio cholerae strain SU129B isolated from Penaeus vannamei: Resistance, virulence, and evolutionary dynamics in bangladeshi aquaculture - Mohammad Sharif Uddin; Kazi Chamonara; Md. Habib Ullah Masum; Afifa Siddiqua; Imam Hossain; Sumaia Sultana; Sajedul Islam (PLoS ONE, 2026)
Vibrio cholerae , a globally significant pathogen, causes both endemic and epidemic cholera and has also been associated with sporadic gastroenteritis and foodborne infections. Shrimp exports are a key source of revenue and employment in Bangladesh. However, Vibrio outbreaks pose serious public health and socio-economic risks through seafood consumption and the spread of antibiotic-resistant genes from aquaculture. The current study investigates the genomic and pathogenic features of the V. cholerae strain associated with seafood, with particular focus on the aquaculture environment of Bangladesh. Using Oxford Nanopore long-read sequencing technology, whole-genome sequencing (WGS) was performed on V. cholerae strain SU129B isolated from pacific white shrimp in Noakhali, Bangladesh, to explore its genetic diversity, antimicrobial resistance, and virulence determinants. The assembled genome exhibited high completeness (93.08%) and contiguity (N50 = 1), along with minimal contamination (1.33%). Average nucleotide identity (ANI) analysis showed 98.13% similarity with the reference V. cholerae strain RFB16, confirming species-level identification. Functional and pathway analyses indicated that the strain possesses a complex network of genes and metabolic systems that contribute to its survival in diverse environments. Analysis of the genome also revealed several biosynthetic gene clusters associated with the production of secondary metabolites, which contribute to osmotic tolerance, and metal acquisition. The genome also harbored multiple antibiotic resistance genes, which confer resistance via efflux systems, target modification, and membrane adaptation mechanisms. Pangenome analysis revealed 8,964 genes, including 2,085 core genes, 429 soft-core genes, 1,431 shell genes, and 5,019 cloud genes, demonstrating considerable genetic diversity and adaptability. Phylogenetic analysis showed a close evolutionary relationship between the shrimp and clinical strains, suggesting possible genome conservation across environmental and clinical isolates. The findings demonstrate that V. cholerae strain SU129B can evolve in aquaculture environments and may serve as a reservoir for virulence and multidrug resistance.